A Vision for Projects Across the Mathematics Curriculum. Issue 4 (20th April 2020) - Cline, K.; Fasteen, J.; Francis, A.; Sullivan, E.; Wendt, T.
Abstract: We consider the use of projects in math courses as a mechanism for promoting coding, communication, and interdisciplinary application of math skills. Final projects play an important role, but we also discuss several alternate types of projects. We describe a model that incorporates projects at all stages across the undergraduate mathematics curriculum. Finally, we provide samples of projects that we have used in selected courses.